ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN LOGAM BERAT (Pb, Cd, As) PADA DEBU DI KECAMATAN SLUKE KABUPATEN REMBANG - Karunia Dwi HPS; Onny Setiani; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
SPM (Suspended Particulate Matter) is a type of particulate that is very small and can cause various diseases. If inhaled can penetrate into the lower respiratory tract and can pass through the bloodstream. This study aimed to analysed environmental health risks due to SPM in district of Sluke. This study0used an analytical research design with an environmental health risk analysis approach. The results of0this study0indicated that the concentrations of the SPM is not exceeded the quality standards set in PP No. 41 of 1999 concerning Air Pollution Control. The results test of the metal content of SPM using ICP-MS, founded 3 metal elements in the dust, namely arsenic (As), lead (Pb), and cadmium (Cd). The results of the calculation of non-carcinogenic risk characteristics of SPM have not been dangerous for exposure through inhalation pathways due to the value of RQ < 1. The calculation results of carcinogenic risk characteristics have not been dangerous for exposure through inhalation pathways because the ECR value is <10-4. From0this study0it can be concluded that the concentration value of SPM does not exceed the established quality standards, and still does not endangered the people lived in Sluke district for the next 30 years for exposure through inhalation.